2019
DOI: 10.1002/ange.201901611
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Microellipsoids that Form Robust String‐Like Assemblies at the Air/Water Interface

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…30 Hence, the ordering of anisotropically shaped particles is influenced by multiple factors such as the particle shape and dimensions and the interfacial properties. 28,31 The effect of softness onto the interfacial behavior of anisotropically shaped microgels was first introduced by Honda et al 32 and further developed in our previous study. 33 Hereby, the interfacial behavior of anisotropic core-shell microgels and more especially the influence of the microgel shell on their deformation, ordering and orientation at the interface were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…30 Hence, the ordering of anisotropically shaped particles is influenced by multiple factors such as the particle shape and dimensions and the interfacial properties. 28,31 The effect of softness onto the interfacial behavior of anisotropically shaped microgels was first introduced by Honda et al 32 and further developed in our previous study. 33 Hereby, the interfacial behavior of anisotropic core-shell microgels and more especially the influence of the microgel shell on their deformation, ordering and orientation at the interface were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…22 In conclusion, the ordering behavior and phase transitions of anisotropic particles depend on multiple factors such as aspect ratio, 17 total size, shape, 19 and hardness. 23 To maintain the benefits of anisotropic structures and expand these with the advantages of soft materials, a combination via a core-shell structure is possible. One way to obtain a soft shell is by synthesizing cross-linked polymers onto an anisotropic hard core.…”
Section: Introductionmentioning
confidence: 99%
“…The cores themselves lose their s-s ordering while the core-shell microgels keep their s-s ordering during the evaporation of an aqueous droplet, hence, a combination of an increase in concentration and a progress in time. 23 Nevertheless, the compression isotherms of hybrid core-shell microgels and the effect on the ordering of different microgel shells have not been investigated yet. In addition, the phase behavior of anisotropic particles is influenced by their aspect ratio, size, wetting angle and contact line.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the past studies have been focusing on spherical composite microgels, there is an emerging interest for anisotropic microgels. The latter can be employed to explore complex self-assembly and dynamics [19][20][21][22][23][24][25] considering that their size, anisotropy, soness and interaction potential can be nely varied with the synthesis conditions and the temperature. Various synthetic strategies have been involved to create such systems.…”
Section: Introductionmentioning
confidence: 99%
“…27 Other studies have shown that a similar approach could be applied to polymeric dumbbells 28 or polystyrene ellipsoids. 25 The second approach relies on the nanoengineering/post processing of composite microgels with a polystyrene core into various shapes such as ellipsoidal 21,22,29 or bowl-shaped particles. [22][23][24] Mesoporous silica materials, formed in solution by mixing a surfactant and a silica source, 30,31 can be synthesised as colloidal porous particles and further used as inorganic templates in the synthesis of hybrid silica/PNIPAM particles.…”
Section: Introductionmentioning
confidence: 99%